Flocking of Multi-Agent System with Nonlinear Dynamics via Distributed Event-Triggered Control - Yanhua Shen (Applied Sciences, 2019)
In this paper, a distributed event-triggered control strategy is proposed to investigate a flocking problem in a multi-agent system with Lipschitz nonlinear dynamics, where triggering conditions are proposed to determine the instants to update the controller. A distributed event-triggered control law with bounded action function is proposed for free flocking. It is proved that the designed event-triggered controller ensures a group of agents reach stable flocking motion while preserving connectivity of the communication network. Lastly, simulations are provided to verify the effectiveness of the theoretical results.